Primary phytochemical screening and spectroscopic assessment of chicory (Cichorium intybus L.) - Zotova, Elizaveta P.; Cherednichenko, Mikhail Yu.; Kalashnikova, Elena A (Zenodo, 2023)
Chicory ( Cichorium intybus L.) is a key source of valuable primary and secondary metabolites (inulin, vitamins, essential oil). The spectrum of medicinal action of chicory includes antimicrobial, anti-inflammatory, choleretic, diuretic, sedative, and appetite stimulating activities. Plant tissue and cell culture allow the production of high yields of plants, biomass, and valuable metabolites throughout the year. In our research, we produced aseptic plants from two Russian breeding ( Yaroslavsky and Petrovsky ), performed their primary phytochemical screening, and established the quantitative content of particular elements and substance groups using IR spectroscopy. It has been found that a high yield of viable aseptic plants of the Yaroslavsky cultivar can be achieved by seed treatment with 8% sodium hypochlorite for 10 minutes or 37% hydrogen peroxide for 5 minutes. For the Petrovsky cultivar, it is advisable to germinate nonsterile seeds and then introduce them into the culture by washing the seedlings in a slightly pink solution of potassium permanganate, followed by sterilization with 8% sodium hypochlorite for 5 minutes and washing with plants the antibiotic solution (0.8% gentamicin) for 15 minutes. All studied classes of compounds (tannins and phenols, flavonoids, saponins, alkaloids, glycosides, reducing sugars, and proteins) are present in aseptic plants of C. intybus however, differences appear depending on the extractants (water and ethanol). IR spectroscopy has shown a higher content of moisture, fiber, and starch in seeds and a higher content of macronutrients, fat, ash, and proteins in aseptic plants.